Cybercrimes and Their Impact on Institutions, Individuals, and Society - Rasem Mseer Jasim; Maan Zaki Kadhim Al Karraawi (International Journal of Law Research and Studies, 2026)
The technological revolution, and especially the communications revolution, is one of the most important developments the world is experiencing. The communications revolution is the primary driver of current developments, but it is not the only driver. The significant advancements in computer technology have greatly contributed to accelerating progress in the field of communications and information. The development in both areas has resulted in the emergence of new tools, inventions, and services in various fields. This technological revolution has led to the emergence of a new type of transaction called electronic transactions, which differ from traditional transactions in terms of the environment in which they take place. Electronic transactions refer to all transactions that take place through electronic equipment such as the telephone, Fax machines, computers, the internet, and more recently through artificial intelligence and its misuse to harm individuals, institutions, and public figures, including through mobile phones. These transactions consist of several basic components. In this paper, we are concerned with presenting a fundamental component: the crimes related to these transactions, or more precisely, the criminal legal rules that govern actions carried out through computers or the internet. Computer and internet crimes, or what are called cybercrimes, are criminal phenomena that sound the alarm, alerting our society to the extent of the risks and losses that can result from them. This is especially true since they are sophisticated crimes that arise and occur in an electronic, or more precisely, digital environment. They are committed by highly intelligent individuals who possess the tools of technical knowledge, causing losses to society as a whole on economic, social, cultural, and security levels, These crimes are also characterized by the difficulty of detection and identifying their perpetrators, and they may involve ordinary individuals, public institutions, or even states at times, in order to achieve reprehensible political and societal objectives. This is what we will try to address in some detail in this research, attempting to lay even a small brick in the regulatory and legislative framework for this issue.